Pax8 has a key role in thyroid cell differentiation - Pasca di Magliano, Marina (The National Academy of Sciences, 2000)
Transformation of rat thyroid cells with polyoma virus middle T antigen results in loss of the thyroid-differentiated phenotype, measured as the expression of the thyroglobulin (Tg), thyroperoxidase (TPO), and sodium/iodide symporter (NIS) genes. Among the transcription factors involved in the regulation of these genes, TTF-1 and TTF-2 were still detected at nearly wild-type levels, while a specific loss of the paired domain transcription factor Pax8 was observed. In this study, we used the PCPy cell line as a model system to study the role of Pax8 in thyroid differentiation. We demonstrate that the reintroduction of Pax8 in PCPy cells is sufficient to activate expression of the endogenous genes encoding thyroglobulin, thyroperoxidase, and sodium/iodide symporter. Thus, this cell system provides direct evidence for the ability of Pax8 to activate transcription of thyroid-specific genes at their chromosomal locus and strongly suggests a fundamental role of this transcription factor in the maintenance of functional differentiation in thyroid cells. Moreover, we show that Pax8 and TTF-1 cooperate in the activation of the thyroglobulin promoter and that additional thyroid-specific mechanism(s) are involved in such a cooperation. To identify the Pax8 domain able to mediate the specific activation of the thyroglobulin promoter, we transfected in PCPy cells three different Pax8 isoforms. The results of such experiments indicate that for the transcriptional activation of thyroid-specific genes, Pax8 uses an as yet unidentified functional domain.